Teaching Leadership - Bahram, Zaitoon (Journal of Social Sciences - Kabul University, 2020)
This article provides valuable insights into various aspects of leadership relevant to effective teaching. The focus is on teaching leadership, defining the concept and explaining the key roles of teachers as leaders. Leadership is not a new phenomenon; throughout history, human beings have demonstrated leadership qualities in different contexts, leading to significant achievements. The same principle applies to education, where teachers can have a substantial impact on organizational development and student learning by demonstrating strong leadership skills. Evidence from international literature suggests that effective leaders exert an indirect yet powerful influence on institutional effectiveness and student achievement